Designing Materials of English for Air Transportation Studies Using Genre-Based Approach - Anita Nur Masyi'ah (Jurnal Bahasa Inggris Terapan, 2025)
This study develops English learning materials tailored for Air Transportation Management students at Sekolah Tinggi Teknologi Kedirgantaraan (STTKD) Yogyakarta using the Genre-Based Approach (GBA) within the framework of English for Specific Purposes (ESP). Motivated by findings of low English proficiency among students, the research adopts the Research and Development (R&D) method following the ASSURE model: Analyze Learners, State Objectives, Select Methods, Utilize Media, Require Learner Participation, and Evaluate and Revise. Needs analysis identified a lack of aviation-specific vocabulary, difficulty in understanding professional registers, and a preference for engaging multimedia resouraces. The resulting product consists of six chapters—Pre-flight, Welcoming Passengers, In-flight, Food and Drinks, Handling Complaints, and Landing Preparation—each integrating GBA stages: Building Knowledge of the Field, Modelling the Text, Joint Construction of the Text, and Independent Construction of the Text. Expert validation and classroom trials confirmed the materials’ validity, relevance, and applicability. The findings indicate that GBA effectively bridges classroom learning with authentic aviation communication contexts, enhancing both language competence and confidence. The study recommends broader implementation of these materials in aviation-focused institutions and inclusion of industry practitioner feedback for further refinement. It is hoped that the teachers can use and promote this approach in teaching English to air transport management students or aviation students in general.